Interpretation of the Problem of Educational use of Aesthetic Views of Eastern Thinkers in Pedagogical Research - Pardaboеvich, Jumaboеv Nabi (Indonesian Journal Publisher, 2024)
The article discusses the issue of learning from the moral, aesthetic, didactic and philosophical views of Eastern thinkers, their research from a mystical, pedagogical, didactic, axiological point of view. Thoughts are expressed about the fact that our spiritual heritage, which has been preserved and developed over the centuries, serves as a program in the education of a perfect human being. This paper delves into the interpretation of the problem concerning the educational utilization of aesthetic perspectives from Eastern thinkers in pedagogical research. It addresses the growing interest in integrating Eastern philosophical aesthetics into educational practices and examines the challenges and opportunities associated with this endeavor. Drawing on a comprehensive review of existing literature, this study explores various Eastern philosophical traditions, such as Taoism, Confucianism, and Zen Buddhism, to elucidate their unique perspectives on aesthetics and education. Additionally, it critically analyzes the implications of incorporating these perspectives into pedagogical frameworks, considering factors such as cultural context, educational goals, and practical implementation strategies. By synthesizing insights from Eastern thought and contemporary educational theory, this paper offers valuable reflections on how educators can effectively leverage Eastern aesthetic views to enrich teaching and learning experiences in diverse educational settings. The findings contribute to a deeper understanding of the intersection between Eastern philosophy and pedagogy, paving the way for further research and practice in this burgeoning field.